Kalu Kumale and the Aesthetics of Wrath: Sculptural Practice, Affective Labor, and Cultural Resilience in Contemporary Nepal - Lama, Nabraj (Global Journal of Cultural Studies, 2025)
This article offers a critical examination of the life, work, and legacy of Kalu Kumale, a pioneering figure in contemporary Nepali sculpture whose oeuvre spans over seven decades. Drawing upon a multidisciplinary qualitative methodology—comprising in-depth interviews, ethnographic observation, and archival analysis—this study investigates how Kumale’s sculptural practice engages with, reinterprets, and transcends traditional Newar iconography. Central to this inquiry are two seminal works, The Corpse of Sati Devi and Two Farmers Fighting, which serve as case studies for exploring the intersection of personal affect, socio-political commentary, and religious symbolism in his art. Framed within the theoretical perspectives of postcolonial aesthetics and affect theory, the article contends that Kumale’s sculptures function as embodied texts that mediate grief, resilience, and communal memory. His integration of wrathful deity motifs and autobiographical narratives exemplifies a form of cultural hybridity that challenges static notions of tradition and modernity. Moreover, Kumale’s sustained engagement in artistic philanthropy and community activism positions him not merely as an artisan, but as a cultural agent who mobilizes art for ethical and social transformation. By situating Kumale within both local traditions and transnational visual discourses, this article contributes to broader debates on indigenous visual sovereignty, cultural resilience, and the evolving role of the artist in postcolonial South Asia.